Delovanje tima za oceno zahtevnejše predelave in prilagoditve vozil - Grabner, Petra (Rehabilitacija (Ljubljana), 2018)
The ability to drive a car is one of the important conditions for social integration for people with permanent consequences of injuries or illness. They need to ensure safe driving of the car by creating a plan for processing or adjusting the vehicle according to their impairment of bodily functions and structures, or depending on their remaining functional abilities. The outpatient clinic for vehicle processing at the University Rehabilitation Institute Soča started operating in November 2014 and runs once a week. The work in the outpatient clinic for assessment of the processing and adaptation of vehicles for persons with permanent consequences of injuries or illness is team-based and is focused on each individual. The team consists of a specialist physician of physiatry, occupational therapist and a technical engineer or technician. Furthermore, I would like to present an example of a more advanced vehicle recovery for an employee of a thirty-five-year-old driver with tetraplegia and a married father of three young children. The following presented is the way of work in the outpatient clinic for the processing of vehicles, the role of the occupational therapist in the team and his participation in the selection of the appropriate vehicle and the processing of the selected vehicle. The purpose of teamwork is to equip people with permanent consequences of injuries or illnesses for the highest possible level of functioning or self-driving of the car, and thus more complete social integration. In the future, our goal is to improve our knowledge in this field and to improve the technical processing of vehicles and the way of work in the outpatient clinic.
Keywords: Automobile Driving; Paraplegia; poškodba hrbtenjače; prilagoditev vozila; rehabilitacija; rehabilitation; spinal cord injuries; teamwork; timska obravnava; vehicle adaptation; vocational rehabilitation; vožnja z avtomobilom